Positive correlation of the serum angiopoietin-like protein 3 levels with the aortic augmentation index in patients with coronary artery disease - Fu YS; Wang JH; Lee CJ; Hsu BG (Dove Medical Press, 2018)
Yu-Shan Fu,1,* Ji-Hung Wang,1,2,* Chung-Jen Lee,3 Bang-Gee Hsu1,4 1School of Medicine, Tzu Chi University, Hualien, 2Division of Cardiology, Buddhist Tzu Chi General Hospital, Hualien, 3Department of Nursing, Tzu Chi University of Science and Technology, Hualien, 4Division of Nephrology, Buddhist Tzu Chi General Hospital, Hualien, Taiwan *These authors contributed equally to this work Purpose: Angiopoietin-like protein 3 (ANGPTL3) plays an important role in lipid metabolism and angiogenesis and is elevated in familial hypercholesterolemia, metabolic syndrome, and insulin resistance. This study aims to evaluate the relationship between the fasting serum ANGPTL3 levels and the aortic augmentation index (AIx) in patients with coronary artery disease (CAD).Materials and methods: Fasting blood samples were obtained from 100 patients with CAD. The AIx was measured using a validated tonometry system (SphygmoCor). The serum ANGPTL3 levels were assessed using a commercial enzyme-linked immunosorbent assay kit.Results: The aortic AIx values were higher in female patients with CAD (P=0.003) than those in male patients with CAD. The univariate linear analysis of the aortic AIx values reveals that the height (r=-0.363; P<0.001) and body weight (r=-0.350; P<0.001) were negatively correlated, whereas the age (r=0.202; P=0.044) and logarithmically transformed ANGPTL3 (log-ANGPTL3, r=0.357; P<0.001) were positively correlated with the aortic AIx values in patients with CAD. The multivariate forward stepwise linear regression analysis of the factors significantly associated with the aortic AIx revealed that the height (β=-0.269; adjusted R2 change=0.123; P=0.007) and serum log-ANGPTL3 level (β=0.259; adjusted R2 change=0.051; P=0.010) were independent predictors of the aortic AIx values in patients with CAD.Conclusion: The fasting serum ANGPTL3 level positively correlated with the aortic AIx values among patients with CAD. Keywords: ANGPTL3, ischemic heart disease, arterial stiffness, height, aortic augmentation index, SphygmoCor